Panel Seemingly Unrelated Regression on Employment in Tourism Sector: Evidence in Central Java Province - Dindha Uswatun Khasanah; Mahrus Lutfi Adi Kurniawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
Job opportunities are the main problem faced by Indonesia because the large of population, high population growth rate and large workforce. The tourism sector has a large multiplier effect on employment and become a potential sector as a source of income for a country or region. By combining cross-section and time-series data in 35 districts and cities in Central Java Province from 2016-2020 and the Seemingly Unrelated Regression Panel approach. The results showed that supporting infrastructure for the tourism sector, such as the number of hotel rooms and the number of restaurants, had an effect on employment in the tourism sector, and a positive effect was shown by the variable number of tourist objects and tourist visits. The coefficient value on the wage variable which is quite large indicates that the elasticity of employment related to wages is quite high. The implication of the research is increasing the quality and quantity of sustainable tourist objects can attract an increase in foreign and domestic tourist visits so as to increase the workforce through the tourism sector. The implication of the study to strengthen among government, private sector and local community to develop sustainable tourism sectors